eIF2α controls memory consolidation via excitatory and somatostatin neurons - Sharma, Vijendra (Nature, 2020)
An important tenet of learning and memory is the notion of a molecular switch that promotes the formation of long-term memory(1,2,3,4). The regulation of proteostasis is a critical and rate-limiting step in the consolidation of new memories(5,6,7,8,9,10). One of the most effective and prevalent ways to enhance memory is by regulating the synthesis of proteins controlled by the translation initiation factor eIF2(11). Phosphorylation of the α-subunit of eIF2 (p-eIF2α), the central component of the integrated stress response (ISR), impairs long-term memory formation in rodents and birds(11,12,13). By contrast, inhibiting the ISR by mutating the eIF2α phosphorylation site, genetically(11) and pharmacologically inhibiting the ISR kinases(14,15,16,17), or mimicking reduced p-eIF2α with the ISR inhibitor ISRIB(11), enhances long-term memory in health and disease(18). Here we used molecular genetics to dissect the neuronal circuits by which the ISR gates cognitive processing. We found that learning reduces eIF2α phosphorylation in hippocampal excitatory neurons and a subset of hippocampal inhibitory neurons (those that express somatostatin, but not parvalbumin). Moreover, ablation of p-eIF2α in either excitatory or somatostatin-expressing (but not parvalbumin-expressing) inhibitory neurons increased general mRNA translation, bolstered synaptic plasticity and enhanced long-term memory. Thus, eIF2α-dependent mRNA translation controls memory consolidation via autonomous mechanisms in excitatory and somatostatin-expressing inhibitory neurons.